Reestructuración técnico administrativa en la empresa Productos Limpia Fácil S.A.S. (2019)
The present degree work carried out a proposal of administrative technical restructuring for the company Productos Limpia Fácil S.A.S., with the objective of improving productivity and profitability of the company, this focused on its internal processes.